#isolationartviews. (2nd July 2020) - Ash, Andy
Abstract : #isolationartviews photographically documents views from a Brighton window over 60 days of the UK first Covid national lock down. It records, reflects and comments upon the social interactions and routines of a seagull, local people and visitors to the artists block during the period of isolation.